Penulisan Kajian Literatur: Solusi Riset Di Masa Pandemi - Siti Rahmatul Aini; Iman Surya Pratama; Wahida Hajrin; Nisa Isnaeni Hanifa; Surya Febrianto; Lalu Husnul Hidayat (Universitas Mataram, 2022)
COVID-19 pandemic condition presents obstacles for lecturers and students of the Pharmacy Study Program in all aspects of life, including the educational aspect. One of the obstacles faced is the limitations of lecturers and students of Pharmacy in conducting field and laboratory research, so that it can have an impact on delays in the implementation of the tridharma. Literature review can be an option in overcoming these obstacles. This community service aims to improve targeting capabilities and design a literature review study as an alternative research solution during a pandemic. The method used in this activity is in the form of delivering material and guided discussions through webinars with the zoom meeting platform and YouTube Livestreaming on the Pharmacy account of the University of Mataram. The webinar is divided into 2 sessions, namely a material presentation session and a clinical session for writing scientific articles with experts. A total of 77 participants attended the activity consisting of lecturers from health groups and pharmacy students. The enthusiasm of the participants was quite high as evidenced by a number of questions submitted in the discussion session. Participants' responses to the activities ranged from 4.2 to 4.7 which indicated that the event was going well with an assessment using a Likert scale from 1 to 5. The components of the assessment included time suitability, material suitability, participants' understanding of the material, moderator behavior, benefits of the event for participants and participant's opinion on the event. The ability of community service participants increases in designing literature studies through the output of articles that will be submitted in reputable journals.